PENERAPAN METODE SCRUM PADA APLIKASI PENGOLAHAN DATA NILAI SISWA SDN 21 BANTAN - Alhaq, Muhammad Hafiz; Enda, Depandi (Jurnal Ilmiah Sistem Informasi, 2025)
The rapid development of information technology has significantly impacted various sectors, including education. SDN 21 Bantan, an elementary school in Bengkalis Regency, faces challenges in managing student grades manually, which is time-consuming and prone to errors, particularly in compiling report cards. This study aims to design a web-based student grade management information system using the Scrum methodology, which is agile and adaptive. The system is designed to assist teachers in processing student grades quickly and generating computerized report cards. The Scrum method is implemented through stages such as Product Backlog, Sprint Planning, Daily Scrum, and Sprint Retrospective. User requirements are identified using the MoSCoW technique, while task estimation is conducted with Planning Poker. The system supports three main types of users: admin, teacher, and principal, each with specific access rights based on their needs. The results show that the developed system facilitates efficient student data management, grade processing, and report card generation. As a web-based system, it allows users to access and manage data anytime and anywhere with an internet connection. This system is expected to improve the effectiveness and efficiency of student grade management at SDN 21 Bantan and serve as a reference for developing similar systems in other educational institutions.